The Honey Bee Gene Bee Antiviral Protein-1 Is a Taxonomically Restricted Antiviral Immune Gene - McMenamin, Alexander J.; Brutscher, Laura M.; Daughenbaugh, Katie F.; Flenniken, Michelle L. (Frontiers in Insect Science, 2021)
Insects have evolved a wide range of strategies to combat invading pathogens, including viruses. Genes that encode proteins involved in immune responses often evolve under positive selection due to their co-evolution with pathogens. Insect antiviral defense includes the RNA interference (RNAi) mechanism, which is triggered by recognition of non-self, virally produced, double-stranded RNAs. Indeed, insect RNAi genes (e.g., dicer and argonaute-2) are under high selective pressure. Honey bees (Apis mellifera) are eusocial insects that respond to viral infections via both sequence specific RNAi and a non-sequence specific dsRNA triggered pathway, which is less well characterized. A transcriptome-level study of virus-infected and/or dsRNA-treated honey bees revealed increased expression of a novel antiviral gene, GenBank: MF116383, and in vivo experiments confirmed its antiviral function. Due to in silico annotation and sequence similarity, MF116383 was originally annotated as a probable cyclin-dependent serine/threonine-protein kinase. In this study, we confirmed that MF116383 limits virus infection, and carried out further bioinformatic and phylogenetic analyses to better characterize this important gene – which we renamed bee antiviral protein-1 (bap1). Phylogenetic analysis revealed that bap1 is taxonomically restricted to Hymenoptera and Blatella germanica (the German cockroach) and that the majority of bap1 amino acids are evolving under neutral selection. This is in-line with the results from structural prediction tools that indicate Bap1 is a highly disordered protein, which likely has relaxed structural constraints. Assessment of honey bee gene expression using a weighted gene correlation network analysis revealed that bap1 expression was highly correlated with several immune genes – most notably argonaute-2. The coexpression of bap1 and argonaute-2 was confirmed in an independent dataset that accounted for the effect of virus abundance. Together, these data demonstrate that bap1 is a taxonomically restricted, rapidly evolving antiviral immune gene. Future work will examine the signal cascade responsible for regulating the expression of bap1 and other honey bee antiviral defense genes, including coexpressed ago-2, and determine whether the virus limiting function of bap1 acts in parallel or in tandem with RNAi.